PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KADER TP PKK KABUPATEN PONOROGO - Zulfiana Arum Purwaningsih (Master of Public Administration, Universitas Slamet Riyadi, 2020)
This study aims to determine and analyze the influence of leadership style andorganizational culture simultaneously on the performance of TP-PKK cadres inPonorogo Regency. The study population was all cadres of the TP-PKK PonorogoRegency. This is a descriptive quantitative study using primary data, obtainedfrom respondents directly using a questionnaire to cadres of TP-PKK PonorogoRegency. The population and number of samples were 49 people. Data collectiontechniques using validity and reliability testing. Analysis techniques throughmultiple regression analysis, t-test, F test, and R2. The results of the analysis areobtained: (1) Leadership (X1) is significant on Performance (Y) in TP-PKKCadres in Ponorogo Regency, this indicates that the better leadership style givento PKK cadres in Ponorogo Regency. (2) Organizational Culture (X2) has apositive and significant effect on performance (Y) of TP-PKK cadres in PonorogoRegency, this is a form of positive things that must be developed, because with theexistence of organizational culture that can spur cadres so that they compete tocontribute to the related services to the maximum and is certainly expected tomake it a habit for the cadres themselves to be loyal to all cadres in PonorogoRegency.